Synergistic growth inhibition by afatinib and trametinib in preclinical oral squamous cell carcinoma models / Yee Pei San - Yee, Pei San (2019)
Oral squamous cell carcinoma (OSCC) remains a challenging disease to manage due to limited efficacious treatments, hence finding more effective treatment approaches remains a priority. Given that the aberrant activation of epidermal growth factor receptor family receptors (ERBB) is a common event in OSCC and high expression of these receptor proteins are often associated with poor prognosis, this rationalizes the approach of targeting ERBB signaling pathways to improve the survival of OSCC patients. However, monotherapy with the pan-ERBB blocker afatinib has shown limited survival benefits. This study was carried out to identify mechanisms of afatinib resistance and to explore potential afatinib-based combination treatment with other targeted inhibitors in OSCC. Anti-proliferative effects of afatinib on a panel of OSCC cell lines were determined via crystal violet cytostatic assay, click-iT 5-ethynyl-2′-deoxyuridine staining and cell cycle analysis. Western blottings were performed to study the underlying mechanism of drug treatment as a single agent or in combination with the MEK inhibitor trametinib. Anti-tumor effects of single agent and combined treatment were evaluated by using OSCC xenograft models. In this study, afatinib inhibited OSCC cell proliferation via cell cycle arrest at the G0/G1 phase, and inhibited tumor growth in xenograft mouse models. Interestingly, the mitogen-activated protein kinase (ERK1/2) was reactivated in vitro, which possibly reduced the effects of ERBB inhibition. Concomitant treatment of OSCC cells with afatinib and trametinib synergized the anti-tumor effects in OSCCbearing mouse models. These findings provide insight into the molecular mechanism of resistance to afatinib and support further clinical evaluation into the combination of afatinib and MEK inhibition in the treatment of OSCC. iv Keywords: Oral squamous cell carcinoma (OSCC), ERBB family kinases, afatinib, trametinib, synergistic growth inhibition